Analysis of School Student Reception on the Application Room as Students' Online Learning Media: Analisis Resepsi Siswa Sekolah terhadap Aplikasi Ruang sebagai Media Pembelajaran Online Siswa - Eka Pratiwi; Ainur Rochmaniah (Academia Open, 2024)
This study aims to investigate the reception of high school students towards the Ruangguru application as an online learning medium. Utilizing a qualitative approach, data collection involved in-depth interviews, observations, and a review of relevant literature, engaging students as participants. The purposive sampling technique determined informants. The findings reveal a hegemonic-dominant position held by 2 informants, indicating their satisfaction with the application, while 8 informants negotiate their position, recognizing the innovative nature of animated content delivery as a solution to monotony. This study sheds light on the diverse perceptions among students, emphasizing the need for adaptive features in online learning platforms. Highlights : The study investigates high school students' perceptions of the Ruangguru application as an online learning medium. Qualitative methods, including in-depth interviews and observations, provide insights into students' experiences with the application. Findings highlight a diversity of responses, with some students endorsing the application's suitability while others negotiate its innovative features as a remedy for boredom. Keywords: reception, Ruangguru application, online learning, high school students, qualitative research